Local Visitors' Perceptions and Opinions on Nature-Based Recreation Development and Management in Phou Khao Khouay National Park, Laos - Sayakoummane, Sousath (2001)
This study looks at the local visitors' perceptions and opinions on natural resource characteristics as recreation resources as well as natural resource management within Phou Khao Khouay National Park, Laos. The specific objectives of the study are to assess visitors' perceptions and opinions on: 1) the importance and meaning of national parks and natural resources, 2) the reasons for using national parks as a recreation resource, 3) natural resource conditions, 4) causes of impacts on natural resources and 5) the natural resource management and management functions of a park agency. Visitors' perceptions and opinions were assessed through on-site questionnaire survey with a total of 313 respondents. The study was conducted in the three popular recreation areas, namely Tad Leuk, Tad Xang and Tad Phou Khao Khouay. The data were analysed using Statistical Package for Social Science (SPSS). Generally, most visitors, especially those with a high level of education, had some knowledge on the importance and meaning of national parks. To the visitors, the establishment of national parks and the uses of natural resources within national parks should place major emphasis on conservation and recreation.